2019
DOI: 10.12968/jowc.2019.28.7.438
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a bacterial fluorescence imaging device in an outpatient wound care clinic: a pilot study

Abstract: Objective: Subsurface bacterial burden can be missed during standard wound examination protocols. The real-time bacterial fluorescence imaging device, MolecuLight i:X, visualises the presence of potentially harmful levels of bacteria through endogenous autofluorescence, without the need for contrast agents or contact with the patient. The intended use of the imaging device is to assist with the management of patients with wounds by enabling real-time visualisation of potentially harmful bacteria. The aim of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
58
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 17 publications
8
58
0
1
Order By: Relevance
“…The addition of bacterial fluorescence information by way of real-time imaging, improved sensitivity and accuracy of assessments for detecting moderate-to-heavy bacterial loads. There is a growing body of evidence to support the use of point-of-care bacterial fluorescence imaging to identify chronic wounds, 31,[57][58][59]30,32,60 burns, 27,29,61,62 surgical 27 and traumatic wounds. 27,28,62 These studies, representing more than 200 imaged wounds, largely concluded that fluorescence information improved detection of clinically-concerning levels of bacteria, thus empowering evidence-based treatment decisions including treatment selection 28,30,57,[62][63][64] and antimicrobial stewardship practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of bacterial fluorescence information by way of real-time imaging, improved sensitivity and accuracy of assessments for detecting moderate-to-heavy bacterial loads. There is a growing body of evidence to support the use of point-of-care bacterial fluorescence imaging to identify chronic wounds, 31,[57][58][59]30,32,60 burns, 27,29,61,62 surgical 27 and traumatic wounds. 27,28,62 These studies, representing more than 200 imaged wounds, largely concluded that fluorescence information improved detection of clinically-concerning levels of bacteria, thus empowering evidence-based treatment decisions including treatment selection 28,30,57,[62][63][64] and antimicrobial stewardship practices.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the percentage of enrolled patients that were true negatives based on microbiology (bacterial load <10 4 CFU/g, 1/19 patients) was surprisingly low, preventing statistical testing of specificity and challenging the ability to determine NPV in this patient cohort (though these have been reported in other studies; recent reports of NPV have ranged from 90 to 100%). 27,60,61 This may have been due, at least in part, to the study's exclusion of patients on antibiotics. Patients actively taking systemic or oral antibiotics would be anticipated to have low bacterial loads.…”
Section: Limitationsmentioning
confidence: 99%
“…Fluorescence imaging detects 87% of the most common wound pathogens, 14 including Pseudomonas aeruginosa, which uniquely produces a cyan fluorescent signature due to endogenous pyoverdine production; a small number of bacterial genera (Streptococcus and Enterococcus) do not emit detectable fluorescence signals. 15 Multiple clinical studies report positive predictive values over 87% when using fluorescence imaging to detect bacteria at loads greater than 10 4 CFU/g 13,16,17 on and beneath the surface of wounds, up to 1.5mm depth. 18 The device also contains digital wound area measurement software that automatically detects the wound border Use of a bacterial fluorescence imaging system to target wound debridement and accelerate healing: a pilot study If bacterial fluorescence remained after aggressive, targeted debridement, clinician employed antimicrobials and/or antibiotics and generates instant, accurate wound measurements (wound surface area, length and width).…”
mentioning
confidence: 99%
“…The MolecuLight i:X imaging device is a novel, handheld, point-of-care diagnostic imaging tool designed to accurately and digitally measure wound areas and to provide objective, real-time evidence on the presence and location of high bacterial loads (both planktonic and in biofilm. [11][12][13][14][15][16] This provides objective documentation, performed at the bedside, during which the device captures an image in a format compatible with most electronic medical records (EMR) systems. The device contains built-in digital wound measurement software and emits a safe violet light which is used for non-invasive, contrast agent free fluorescence imaging to identify regions with concerning levels of bacteria in real-time.…”
mentioning
confidence: 99%